(untitled) (LIS TODAY, 2024)
Grey literature has a pivotal role in the research study. It offers valuable insights that are often overlooked in traditional academic publications. Non conventional published materials such as reports, theses, and conference proceedings are examples of grey literature. This study investigates the utilization of grey literature by social science students in India, and the findings reveal that it is widely utilized due to its accessibility, relevance to local contexts, and provision of current information. The recent publication of grey literature is used more than the earlier published literature. Researchers frequently rely on government reports and NGO publications. This study encourages researchers to cite grey literature in their research.